Occurrence of enteropathogenic bacteria in birds of prey in Italy. (1st March 2018) - Gargiulo, A.; Fioretti, A.; Russo, T.P.; Varriale, L.; Rampa, L.; Paone, S.; De Luca Bossa, L.M.; Raia, P.; Dipineto, L.
Abstract : Abstract: The importance of wild birds as potential vectors of disease has received recent renewed empirical interest, especially regarding human health although information regarding the enteropathogenic bacteria in birds of prey continue to be scant. This study was performed with the aim to evaluate the occurrence of enteropathogenic bacteria (i.e. Campylobacter spp. Escherichia coli, Salmonella spp.) in birds of prey carcasses in Southern Italy. The results of the present study showed a prevalence of 33·1% (49/148) for Campylobacter spp. where all positive isolates (49/49) were identified as Campylobacter jejuni, and among these positive 12/49 were also identified as Campylobacter coli . Thus, 12/49 birds of prey showed mixed infections for both Campylobacter species. Differences in Campylobacter spp. prevalence between diurnal and nocturnal birds were statistically significant ( P = 0·016). Escherichia coli showed a prevalence of 6·8% (10/148) and were serogrouped as O26 ( n = 3), O55 ( n = 2), O145 ( n = 5). Salmonella spp. showed a prevalence of 6·8% (10/148) and were serotyped as S . Napoli ( n = 4), Salmonella salamae ( n = 3) and S . Typhimurium ( n = 3). Although wildlife disease outbreaks have often been underreported in the broader context of global epidemiology, results of the present study suggest that birds of prey may serve as a reservoir of pathogens for livestock and human health, acting at the animal‐human‐ecosystem interface. Significance and Impact of the Study: This study confirms the role of birds of prey as a reservoir of enteropathogenic bacteria (i.e. Campylobacter spp., Escherichia coli, Salmonella spp.). Wild birds can contaminate environment with their faeces and play a crucial role in the transmission of pathogens to poultry and livestock farms and aquifers supplying water to humans. Furthermore, wild birds could disseminate pathogens within rescue and rehabilitation centres where they are admitted.